Intra-Individual Variability of Aldosterone Concentrations in Primary Aldosteronism: Implications for Case Detection - Yozamp, Nicholas (Hypertension, 2020)
Primary aldosteronism is an underdiagnosed cause of hypertension. Although inadequate screening is one reason for underdiagnosis, another important contributor is that clinicians may inappropriately exclude the diagnosis when screening aldosterone concentrations fall below traditionally established thresholds. We evaluated the intra-individual variability in screening aldosterone concentrations and aldosterone-to-renin ratios, and how this variability could impact case detection, among 51 patients with confirmed primary aldosteronism who had two or more screening measurements of renin and aldosterone on different days. There were a total of 137 screening measurements with a mean of 3 (range 2–6) per patient. The mean intra-individual variability, expressed as coefficients of variation, was 31% for aldosterone and 45% for the aldosterone-to-renin ratio. Aldosterone concentrations ranged from 4.9 to 51 ng/dL; 49% of patients had at least one aldosterone measurement below 15 ng/dL, 29% had at least two aldosterone measurements below 15 ng/dL, and 29% had at least one measurement below 10 ng/dL. Individual aldosterone-to-renin ratios ranged from 8.2 to 427 ng/dL per ng/mL/h; 57% had at least one ratio below 30 ng/dL per ng/mL/h, 27% had at least two ratios below 30 ng/dL per ng/mL/h, and 24% had at least one ratio below 20 ng/dL per ng/mL/h. Aldosterone concentrations and aldosterone-to-renin ratios are highly variable in patients with primary aldosteronism, with many screening values falling below conventionally accepted diagnostic thresholds. The diagnostic yield for primary aldosteronism may be substantially increased by re-calibrating the definition of a ‘positive screen’ to include more liberal thresholds for aldosterone and the aldosterone-to-renin ratio.